Case Report: Successful conversion and salvage resection of huge hepatocellular carcinoma with portal vein tumor thrombosis and intrahepatic metastasis via sequential hepatic arterial infusion chemotherapy, lenvatinib plus PD-1 antibody followed by simultaneous transcatheter arterial chemoembolization, and portal vein embolization - Luo, Xin; Chang, Rui-zhi; Kuang, Dong; Yuan, Mingming; Li, Gan-xun; Zhang, Bixiang; Wang, Yan-jun; Zhang, Wan-guang; Ding, Ze-yang (Frontiers in Immunology, 2023)
Background: Advanced hepatocellular carcinoma (HCC) shows poor prognosis. Combined hepatic artery infusion chemotherapy (HAIC), lenvatinib and PD-1 antibody therapy show promising effect in treating advanced HCC, and salvage hepatectomy further promotes the overall survival in patients who were successfully converted after combined therapy. However, salvage major hepatectomy is not always amenable due to insufficient future liver remnant volume (FLV). Case presentation: We report the case of a 59-year-old man with a huge HCC as well as multiple intrahepatic foci and portal vein tumor thrombosis at his right hemi-liver. Genomic and pathologic analyses of HCC tissue revealed a TMB-high, TPS and CPS-high cancer, with mutated DNA damage repair gene FANCC. These results suggested this patient may benefit from chemotherapy and immunotherapy. Thus, he received combined HAIC, lenvatinib and PD-1 antibody treatment and showed a quick and durable response. After successful downstaging, this patient was evaluated as not suitable for salvage hepatectomy due to the low FLV. He then received simultaneous transcatheter arterial chemoembolization (TACE) and portal vein embolization (PVE). The FLV increased to meet the criteria of salvage hepatectomy. Finally, this patient underwent right hemi-hepatectomy without any severe perioperative complications. In addition, no tumor recurrence occurred during the 9-month follow-up period after surgery. Conclusion: Combined HAIC, lenvatinib and PD-1 antibody therapy, followed by simultaneous TACE and PVE, is a safe and effective conversion therapy that promotes tumor necrosis and increase FLV in patients with advanced HCC.